LEGISLATIVE AND LEGAL REGULATION OF FEED AND CIRCULATION OF FEED - Приліпко, Тетяна; Букалова, Наталья; Руснак, Леся; Богатко, Альона; Вакуленко, Назар (SWorldJournal, 2025)
The issues of legislative regulation and legal basis for the management of feed for productive animals, their safety, in the context of direct interconnection with the safety of animal products for human consumption and direct impact on its health, laid d